2005
DOI: 10.1159/000087508
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 lysine 4 dimethylation is enriched on the inactive sex chromosomes in male meiosis but absent on the inactive X in female somatic cells

Abstract: Inactivation of the X chromosome occurs in female somatic cells and in male meiosis. In both cases, the inactive X chromosome undergoes changes in histone modifications including deacetylation of core histone proteins and enrichment with histone H3 lysine 9 (H3-K9) dimethylation. In this study we show that while the inactive X in female somatic cells is largely devoid of H3-K4 dimethylation, the inactive X in male meiosis is enriched with this modification. However, the inactive X chromosome in female somatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 63 publications
2
23
0
1
Order By: Relevance
“…21,31 However, as expected the X and Y chromosomes become enriched with the repressive modification H3K9me2 from the late pachytene stage to the early spermatid stage. 21 Analysis of the male X and Y during spermatogenesis using an antibody for RNA polymerase II (H5) when phosphorylated at serine 2 suggest that there are several regions that escape XY inactivation (XYi), which begins at the pachytene stage of meiosis.…”
Section: Discussionsupporting
confidence: 75%
“…21,31 However, as expected the X and Y chromosomes become enriched with the repressive modification H3K9me2 from the late pachytene stage to the early spermatid stage. 21 Analysis of the male X and Y during spermatogenesis using an antibody for RNA polymerase II (H5) when phosphorylated at serine 2 suggest that there are several regions that escape XY inactivation (XYi), which begins at the pachytene stage of meiosis.…”
Section: Discussionsupporting
confidence: 75%
“…Somehow, lack of HR6B affects H2A T120ph , and this may subsequently lead to increased H3 K4m1 and H3 K4m2 , specifically in the XY body. Previously, Khalil and Driscoll (Khalil and Driscoll, 2006), reported that H3 K4m2 is upregulated on the silent XY body of wild-type diplotene spermatocytes. Our data confirm their findings, and we show that in Hr6b-knockout spermatocytes this modification is further upregulated on X and Y.…”
Section: Discussionmentioning
confidence: 98%
“…However, the X and Y chromosomes are continually remodelled during the transition between meiosis and spermiogenesis, and histone modifications associated with transcriptionally active chromatin [e.g. histone acetylation and histone H3 dimethylated on lysine 4 (H3K4me2)] are also enriched on PMSC in round spermatids (Baarends et al, 2007;Greaves et al, 2006;Khalil and Driscoll, 2006). These epigenetic changes could explain why XY spermatid silencing is less complete than MSCI, and might reflect a need to retain expression of some X-and Yencoded genes that are essential for spermiogenesis.…”
Section: Introductionmentioning
confidence: 99%